Factors Associated with the Lack of Adherence to Drug Therapy in Diabetic Patients - Rivas, Alba (2019)
According to the World Health Organization, there are more than 347 million people living with diabetes, being one of theleading causes of death in our days. Diabetes mellitus is a chronic metabolic disorder characterized by an increase in glycemiavalues above normal, which is accompanied by late complications derived from progressive damage in kidney, retina, vessels,heart, and nervous system. The best way to avoid these complications is adherence to treatment. However, the lack of treatmentcontinuity is very frequent. This paper demonstrated that in 76% of the cases, patients with diabetes do not accomplish theprescribed treatment. The main causes of this situation are related to the patient?s habits (since diabetes has no symptoms,the patients skip doses) and to the health system (due to the lack of free drug provision, patients do not have access to thetreatment). From this data, health country authorities initiated a program to aware patients of the importance to accomplish thetreatment and provided free drug for those patients